Borehole Hydrophone Aquisition - Some pitfalls and solutions - Greenwood, Andrew; Dupuis, Christian; Kepic, Anton; Urosevic, Milovan (EAGE, 2011)
Hydrophones are highly sensitive broadband pressure sensors. They are slim-line, lightweight, rapidly deployable and do not require clamping. Strings of 24 – 48 receivers can be manufactured for the same cost as a single slim-line 3C shuttle. The passive hydraulic coupling and suspension within the water column employed by the hydrophones lead to specific acquisition issues due to noise sources related to cable and borehole seismic modes. With the use of a 24 channel hydrophone string, over several surveys in predominately mineral exploration boreholes, we have investigated suppression of these noise sources. Improvement of hydrophone coupling to the formation is achieved through higher viscosity drilling fluids. It is also encouraging that very high quality converted shear waves can be recorded with hydrophones. We show that due to easy deployment and rapid acquisition time it is possible to utilise very fine hydrophone increment of just 1m which enables a proper registration of tube waves and hence their effective removal. Finally we test our hydrophone array in a complex hard rock environment. Using a known geological model, through extensive elastic modelling we prove the validity of an ultra-high resolution VSP image constructed from hydrophone data.